2014
DOI: 10.1016/j.virusres.2014.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Transmissible gastroenteritis virus and porcine epidemic diarrhoea virus infection induces dramatic changes in the tight junctions and microfilaments of polarized IPEC-J2 cells

Abstract: Viral infection converts the normal constitution of a cell to optimise viral entry, replication, and virion production. These conversions contain alterations or disruptions of the tight and adherens junctions between cells as part of their pathogenesis, and reorganise cellular microfilaments that initiate, sustain and spread the viral infections and so on. Using porcine epidemic diarrhoea virus (PEDV), transmissible gastroenteritis virus (TGEV) and a model of normal intestinal epithelial cells (IPEC-J2), we re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 35 publications
(35 reference statements)
1
82
1
Order By: Relevance
“…PEDV, transmissible gastroenteritis virus (TGEV) and porcine rotavirus are major swine pathogens that cause viral gastroenteritis, and the target of these viruses is the intestinal epithelium (Liu et al, 2010;Zhao et al, 2014). Therefore, IECs are optimal for studying the pathogenic mechanisms of these viruses, owing to their strong similarities with primary intestinal epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…PEDV, transmissible gastroenteritis virus (TGEV) and porcine rotavirus are major swine pathogens that cause viral gastroenteritis, and the target of these viruses is the intestinal epithelium (Liu et al, 2010;Zhao et al, 2014). Therefore, IECs are optimal for studying the pathogenic mechanisms of these viruses, owing to their strong similarities with primary intestinal epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to occludin, the tight junction protein claudin-1 is tightly related to the infection of dengue virus, HCV, West Nile virus, and others (25)(26)(27)(28). During PEDV infection, it has been demonstrated that structural destruction and disorganization of tight junctions are observed (12,29). However, the role of tight junctions in PEDV infection has not yet been defined.…”
mentioning
confidence: 99%
“…After infection of polarized porcine intestinal epithelial cells (IPEC-J2), TGEV and PEDV induced MAPK activation to affect cell microfilaments and alter epithelial barrier integrity (Zhao et al, 2014). In both TGEV and PEDV infection, ERK activation is required for efficient virus replication.…”
Section: Host Cell Pathways Involved In Pathogenesismentioning
confidence: 99%